Role of chest X-ray in citing central venous catheter tip: A few case reports with a brief review of the literature - Achuthan Nair Venugopal; Rachel Cherian Koshy; Sumod M Koshy (Wolters Kluwer Medknow Publications, 2013)
Central venous catheter (CVC) insertions are increasingly performed in surgical patients and intensive therapy. A simple and invasive procedure performed under strict sterile precautions with complications ranging from arrhythmias; infections; and life-threatening complications such as pericardial tamponade, cardiac perforation and even death. A post-procedure chest X-ray (CXR), though does not accurately assess the tip of the catheter in relation to the superior vena cava (SVC) and right atrium (RA), can detect malpositions, safety of catheter tip, pneumothorax and kinking. We would like to share some of the malpositions we encountered in our centre, their management and a brief review of the literature on optimal catheter tip location.